2022
DOI: 10.1002/aoc.6956
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of ferrocene‐based magnetic nanoparticle and investigation of its catalytic ability in the synthesis of novel 6‐[(morpholin‐4‐yl)methyl] substituted pyrano[3,2‐b]pyran derivatives

Abstract: In this work, we designed and synthesized the Fe 3 O 4 @SiO 2 @(CH 2 ) 3 -Im-bisethylFc (CH 3 CO 2 ) as a new catalyst for three-multicomponent reaction (t-MCR), which is a silica-coated Fe 3 O 4 nanoparticle supported with bisethylferrocene-containing IL. All of the prepared nanoparticles were specified using FT-IR spectroscopy, FE-SEM, XRD, TEM, and EDX techniques. The activity of the final modified nanoparticle as MCR catalyst was tested in the one-pot procurement of novel pyran derivatives through a t-MCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The bis-ferrocene-based magnetic nanocatalyst was prepared in three steps: Initially, the [Fe 3 O 4 @SiO 2 -Imidazole] nanoparticle and 5-iodo-2,2-bis{EthylFerrocenyl} pentane were prepared according to reference procedures, 36,55 respectively. In continue, 0.6 g of [Fe 3 O 4 @SiO 2 -Imidazole] nanoparticles in 60-mL dry toluene were sonicated for 30 min.…”
Section: Synthesis Of [Fementioning
confidence: 99%
“…The bis-ferrocene-based magnetic nanocatalyst was prepared in three steps: Initially, the [Fe 3 O 4 @SiO 2 -Imidazole] nanoparticle and 5-iodo-2,2-bis{EthylFerrocenyl} pentane were prepared according to reference procedures, 36,55 respectively. In continue, 0.6 g of [Fe 3 O 4 @SiO 2 -Imidazole] nanoparticles in 60-mL dry toluene were sonicated for 30 min.…”
Section: Synthesis Of [Fementioning
confidence: 99%
“…Indeed, magnetically modified cellulose derivatives are gaining increasing interest in the field of organic synthesis because of the higher odds of increasing molecular structural diversifications [ 26 , 27 , 28 ]. Several recent studies have reported the use of new catalytic systems to produce a new range of molecules [ 29 , 30 , 31 ]. In recent years, imidazole scaffolds have been a vital class of important heterocycles due to their abundance in natural products and their extensive use in medicinal chemistry [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…[12] To improve the catalytic efficiency of MNPs and provide anchoring groups for the immobilization of catalysts, several types of functionalization reactions have been used. [13][14][15][16][17][18] The grafted functional groups affect the catalyst's composition and morphology and consequently the reactivity and selectivity of the magnetic system. For instance, Veisi et al developed green and efficient nanocatalysts based on Chitosan-Fe 3 O 4 @SiO 2 -NH 2 nanocomposites decorated with palladium nanoparticles for Suzuki-Miyaura coupling reactions and for the reduction of 4-nitrophenol pollutant to 4-aminophenol within a short time.…”
Section: Introductionmentioning
confidence: 99%